Continuous alumina fiber-reinforced yttria-stabilized zirconia composites with high density and toughness. Issue 4 (April 2020) - Li, Xuewu; Fan, Xiaohui; Ni, Na; Zhao, Xiaofeng; Li, Chuanwei; Xiao, Ping
Abstract: Continuous alumina fiber-reinforced yttria-stabilized zirconia (YSZ) composites with a LaPO4 fiber coating were fabricated by slurry infiltration and spark plasma sintering (SPS). The LaPO4 coating was deposited on the reinforcement alumina fabrics by a modified sol-gel method. The YSZ slurry with good dispersion and stability was prepared by optimizing the pH value, dispersant addition and ball milling time. The fabricated composite with a high density of ∼ 92 % has a good flexural strength of 277 ± 43 MPa, and a superior fracture toughness of 15.93 ± 0.75 MPa·m 1/2 exhibiting a non-brittle failure behavior. It was found that the LaPO4 coating reduced the residual stress near the fiber/matrix interface to 131 ± 41 MPa, which was 369 ± 63 MPa in the composite without the fiber coating. The LaPO4 coating renders a weak interphase to improve the composite toughness by activating several toughening mechanisms including crack deflection, fiber debonding and pullout, and delamination behavior.